(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
The article analyzes the classification of pedagogical communication styles used by pedagogues during training. In addition, by using the method of pedagogical communication correctly, the manners of preschoolers, aspects related to information acquisition are reflected in the article. The impact of pedagogical communication methods on the mastering process in the teacher’s professional activity has been thoroughly analyzed.